Three poems between hidden opposition and alienation - Al-Aroud, Ahmad; Hilal, Ahmad (Al-Adab Journal, 2024)
This study comes to demonstrate the relationship between three poems: (Lamia) the Umayyad poet Al-Ra’i Al-NumeiriAnd two poems by Muhammad Mahdi Al-Jawahiri (Nagit Lebanon) and (ASEF FAME), which is the relationship of opposition and Extraction. As for his poem (ASEF FAME), its context and some of its verses were derived from the poem (Nagit Lebanon). The study followed in reaching that balance between these poems by standing on the common theme, meter, rhyme, narration, and repetition in the verses between these poems.